Video-EEG Study of Seizure Prevalence in Comatose PICU Patients - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The prevalence of epileptic seizures (clinical and subclinical) in 100 consecutive comatose children aged 2 months to 17 years in the pediatric ICU was determined using continuous video-EEG (v-EEE) monitoring, in a prospective study at The Royal Children's Hospital, Melbourne, Australia.